STUDI GENDER: PEREMPUAN DAN ANTI KORUPSI - Rachel Winati; Lisa Savitri Nataleni, Nuvia Cristy, Sarmauli (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This research focuses on anti-corruption efforts by women within the framework of gender studies. The objective is to examine women's roles in corruption and their contributions to anti-corruption initiatives. The methodology employed is qualitative research utilizing a literature review approach. The first step involves selecting relevant sources from journals, books, and articles concerning women and anti-corruption. After gathering the literature, an analysis is conducted to understand the role of women in combating corruption, and the information is systematically organized using clear language. The findings indicate that gender equality is a proven factor in reducing corruption. Countries with higher levels of gender equality tend to have lower rates of corruption. Empowering women in public decision-making and leadership can strengthen more transparent and accountable anti-corruption systems. Women play a vital role in combating corruption not only as primary actors but also as moral advocates, encouraging society toward a cleaner, more honest, and corruption-free culture